Management of alliance portfolios and the role of the board of directors. Issue 2 (3rd March 2016) - Castro, Ignacio; Galán, José L.; Casanueva, Cristóbal
Abstract: The objective of the present work consists in testing whether the strategic involvement of boards of directors has a positive influence on the development of alliance portfolio management capability and on the value that the alliance portfolio generates. A variance-based structural equation modelling (Partial Least Squares) has been applied to a sample constituted by 139 top Spanish companies. Our analysis shows that the strategic involvement of the board of directors has a positive and influence on the management of alliance portfolios, thereby influencing the value of that portfolio in an indirect way. Unlike previous literature, this study links the functions of the board of directors to organizational capabilities, connecting the literature on corporate governance and on management of alliance portfolios.